An empirical study of the relationship between knowledge sharing and IS IT strategic planning (ISSP) - Pai, Jung-Chi (Management decision, 2006)
Purpose - The main purpose of this study is to examine the relationship between knowledge sharing behaviour and the effectiveness of IS IT strategic planning (ISSP). Furthermore, we explore the factors influencing knowledge-sharing behaviour among stakeholders in the ISSP process.Design methodology approach - To test the relationships between the constructs in the research model, data were collected by a questionnaire survey sent to the IS IT executives of 805 large companies in Taiwan.Findings - Survey results indicate that knowledge sharing behaviour influences the effectiveness of ISSP. Certain factors are also found to influence knowledge sharing behaviour among stakeholders in the ISSP process.Research limitations implications - Future research should focus on the following areas, as motivated by limitations of the present study. First, future researchers might attempt to understand the conclusions about the knowledge sharing factors of this research through structured interviews in case studies of IS directors from ongoing or recently completed ISSP projects. Researchers might ask subjects why these factors are associated with the effectiveness of ISSP. Second, future researchers could consider more general factors that affecting knowledge sharing behaviour such as task coordination, rewards and political behaviour. Third, the subjects of this study are IS executives in Taiwan. Cultural differences may exist between Taiwan and other countries. Future research should be similarly carried out in other countries.Practical implications - To achieve the consistently planning objectives, knowledge sharing is necessary to IS IT strategic planning. Numerous organizational mechanisms exist that can enhance knowledge sharing and transfer, including IT steering committee and strategic IS IT team. Furthermore, organizations could apply both of group interaction mechanism and knowledge management mechanism to promote the formulation of organizational learning environment and fit the organizational context during IS IT strategic planning.Originality value - The study shows a growing amount of empirical work that has been conducted examining the relationship between ISSP and organizational context. However, there has been little empirical research that investigates the relationship between knowledge sharing behaviour among stakeholders and the effectiveness of ISSP. The results of this study will be of interest to business managers or strategic planners who are initiating or conducting information systems strategic planning exercises, ant to researchers in the field of information systems management and planning.